The Low-Mass End of the MBH/Mhost Relation in Quasars - Roberto Decarli; Renato Falomo; Jari K. Kotilainen; Tomi Hyvönen; Michela Uslenghi; Aldo Treves (Advances in Astronomy)
The MBH-Mhost relation in quasars has been probed only in a limited parameter space, namely, at MBH∼109 M⊙ and Mhost∼1012  M⊙. Here we present a study of 26 quasars laying in the low-mass end of the relation, down to MBH∼107 M⊙. We selected quasars from the SDSS and HST-FOS archives, requiring modest MBH (as derived through the virial paradigm). We imaged our sources in H band from the Nordic Optical Telescope. The quasar host galaxies have been resolved in 25 out of 26 observed targets. Host galaxy luminosities and stellar masses are computed, under reasonable assumptions on their star formation histories. Combining these results with those from our previous studies, we manage to extend the sampled parameter space of the MBH-Mhost relation in quasars. The relation holds over 2 dex in both the parameters. For the first time, we are able to measure the slope of the MBH-Mhost relation in quasars. We find that it is consistent with the linear case (similarly to what observed in quiescent galaxies). We do not find any evidence of a population of massive black holes lying below the relation.